A starch-polyhydroxyalkanoate-based degradable composite material and preparation method thereof
By performing epoxial treatment of vegetable oil and reacting with starch, it gives starch hydrophobic characteristics, and mixes with polycaticated fatty acid ester and other materials to solve the problem of poor starch and PHA compatibility. Stability achieves better mechanical properties and adaptability.
Patent Information
- Application Number
- CN202410966277.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-18
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-07-18
AI Technical Summary
Starch and polyhydroxy fatty acid esters (PHA) have poor compatibility during blending, resulting in poor processing performance of the material, limiting the improvement of material performance.
By epoxy the vegetable oil, prepare epoxy oxide oil, and use it to react with the desertor starch to give starch hydrophobic characteristics. Then mix the modified starch with polycaticated fatty acid ester, microcrystalline wax and hydrophobic plasticizer. Materials of hydroxyl fatty acid ester.
Improved the compatibility and thermal stability of starch-polyhydroxyalkanoate-based composite materials, allowing them to exhibit better mechanical properties and adaptability under a variety of processing methods, while maintaining the biocompatibility and Degradable properties.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer material preparation, in particular to a starch-polyhydroxyalkanoate-based degradable composite material and a preparation method thereof. Background Art
[0002] The widespread use of plastic products has led to serious environmental problems, such as "white pollution" and the accumulation of long-term, difficult-to-degrade plastic waste. These problems not only affect the beauty of natural landscapes, but also have long-term negative impacts on soil, water bodies and ecosystems. Therefore, the development of new degradable materials to replace traditional plastics has become a research hotspot in the fields of materials science and environmental science. Starch, as a renewable resource widely present in nature, has the advantages of biodegradability, renewability and low cost. However, pure starch materials have obvious deficiencies in mechanical properties, water resistance and thermal stability, which limits their application in various fields. In order to overcome these limitations, researchers have begun to explore the composite technology of starch with other degradable polymers to improve its comprehensive properties. Polyhydroxyalkanoates (PHA) are a class of bio-based polyesters synthesized by microorganisms through a fermentation process with good biodegradability and biocompatibility. PHA materials can be naturally degraded into water and carbon dioxide in soil and water bodies, which is environmentally friendly and pollution-free. In addition, PHA materials also exhibit good mechanical properties and processing properties, which makes it an ideal choice for composite with starch.
[0003] However, due to the large difference in properties between starch and PHA, the compatibility between the two is poor during the blending process. Excessive addition of PHA to starch will lead to poor processing performance of the material, resulting in limited improvement in material performance. In addition, since most methods for processing polymers at this stage are mainly melt granulation in an extruder and then used, the PHA component will degrade during the melt extrusion process, so it is necessary to increase the amount of PHA added to achieve the expected performance improvement effect. Therefore, a new starch-polyhydroxyalkanoate-based composite material and its preparation method are needed to improve the bonding effect and performance of the material and make it adaptable to more processing methods. Summary of the invention
[0004] The object of the present invention is to provide a starch-polyhydroxyalkanoate-based degradable composite material and a preparation method thereof, so as to solve the problems raised in the background technology. Vegetable oil is epoxidized to prepare epoxidized vegetable oil, and the epoxy groups on the epoxidized vegetable oil react with the hydroxyl groups on the debranched starch, and the hydrophobic long chains of the vegetable oil are grafted on the starch surface to give the starch hydrophobic properties, and the modified starch-epoxidized vegetable oil composite system is obtained by mixing with the residual epoxidized oil system of the reaction. The system is mixed with a hydrophobic plasticizer such as a polyhydroxyalkanoate-based and microcrystalline wax, a citrate ester and a lactate ester, and then melt-extruded in an extruder to prepare a starch-polyhydroxyalkanoate-based degradable composite material, the components have good compatibility, and the material has better thermal stability.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] A method for preparing a starch-polyhydroxyalkanoate-based degradable composite material comprises the following steps:
[0007] S1, epoxidizing the vegetable oil to obtain epoxidized vegetable oil;
[0008] S2, hydrophobically modifying starch using epoxidized vegetable oil to obtain a modified starch-epoxidized vegetable oil composite system;
[0009] S3. Mix the modified starch-epoxidized vegetable oil composite system, polyhydroxyalkanoate and hydrophobic plasticizer in a blender at a mass ratio of (50-60):(10-20):(5-10) at a speed of 100-150 rpm for 5-10 minutes, add microcrystalline wax and then increase the stirring speed to 500-700 rpm, and continue mixing for 10-20 minutes to obtain a mixture; seal the mixture and place it at room temperature for 12-36 hours, and then extrude and granulate it through a twin-screw granulator at a screw speed of 30-60 rpm to obtain a starch-polyhydroxyalkanoate-based biodegradable composite material.
[0010] Further, in step S1, the epoxidized vegetable oil is prepared by the following steps:
[0011] Sulfuric acid is added to the vegetable oil and stirred evenly, then formic acid is added to the system, the system temperature is increased to 40-50°C and stirred at a rate of 300-500rpm for 5-20 minutes, then the system temperature is increased to 55-65°C, then a hydrogen peroxide solution is added dropwise, and after the addition is completed, the reaction is continued for 3 hours, then the mixture is allowed to stand and separate, and the oil phase is collected; the oil phase is washed with a sodium hydroxide solution and a saturated salt water solution in turn to obtain the epoxidized vegetable oil.
[0012] Furthermore, the volume ratio of sulfuric acid, formic acid hydrogen peroxide solution and vegetable oil is (1-3):(5-7):(30-40):50.
[0013] Further, in step S2, the modified starch-epoxidized vegetable oil composite system is prepared by the following steps:
[0014] Debranched starch is added to tetrahydrofuran, and stirred at room temperature until uniform to obtain a starch suspension; then an inhibitor is added to the system, and the system temperature is increased to 80-100° C., and then epoxidized vegetable oil is added, and the reaction is stirred for 5-20 hours, and then the system is cooled to room temperature and the filtrate and the filtrate are collected respectively, and the filtrate and the filtrate are washed with tetrahydrofuran respectively, and the washed filtrate is dried, and the organic phase is removed from the washed filtrate, and the filtrate is remixed with the filtrate to obtain a modified starch-epoxidized vegetable oil composite system.
[0015] Further, in step S2, the modified starch-epoxidized vegetable oil composite system is prepared by the following steps:
[0016] Debranched starch is added to tetrahydrofuran, and stirred at room temperature until uniform to obtain a starch suspension; then an inhibitor is added to the system, and the system temperature is increased to 80-100° C., and then epoxidized vegetable oil is added, and the reaction is stirred at a rate of 30-60 rpm for 5-20 hours, and the filtrate and the filtrate are cooled to room temperature, and the filtrate and the filtrate are respectively collected, and the filtrate and the filtrate are respectively washed with tetrahydrofuran, and the washed filtrate is dried at 90° C., and the organic phase is removed from the washed filtrate, and the filtrate is remixed with the filtrate to obtain a modified starch-epoxidized vegetable oil composite system.
[0017] During the above reaction process, the epoxy groups in the epoxidized vegetable oil react with the hydroxyl groups on the starch surface, and the hydrophobic segments of the vegetable oil are grafted on the starch surface, thereby improving the hydrophobicity of the starch. The starch completes the pre-gelatinization step during the heating process, and the inhibitor in the system is dissolved by filtration and separation using tetrahydrofuran. Subsequently, the tetrahydrofuran solvent in the system is removed by heating, drying and separation, and then the modified starch-epoxidized vegetable oil composite system is obtained by remixing with the soybean oil filtrate.
[0018] Furthermore, the mass ratio of debranched starch, epoxidized vegetable oil and inhibitor is (0.5-1):(1-5):(0.0105-0.025).
[0019] Furthermore, the polymerization inhibitor is obtained by mixing triphenylphosphine and hydroquinone in a mass ratio of (10-20): (0.5-5).
[0020] Furthermore, in step S3, the hydrophobic plasticizer is at least one of a citrate plasticizer and a lactate plasticizer.
[0021] Furthermore, the hydrophobic plasticizer is at least one of acetyl triethyl citrate, triethyl citrate, citrate esters, ethyl lactate, propyl lactate, isopropyl lactate and butyl lactate.
[0022] Furthermore, in step S3, the amount of microcrystalline wax used is 1-5wt% of the total mass of the modified starch-epoxidized vegetable oil composite system, polyhydroxyalkanoate and hydrophobic plasticizer.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] In the technical scheme of the present invention, the vegetable oil is epoxidized to prepare epoxidized vegetable oil, and the epoxy groups on the epoxidized vegetable oil react with the hydroxyl groups on the debranched starch to graft the hydrophobic long chains of the vegetable oil on the starch surface to give the starch hydrophobic properties, and the modified starch-epoxidized vegetable oil composite system is mixed with the remaining epoxidized oil system of the reaction. The system is mixed with a hydrophobic plasticizer such as a polyhydroxyalkanoate group and microcrystalline wax, a citrate ester and a lactate ester, and then melt-extruded in an extruder to prepare a starch-polyhydroxyalkanoate-based degradable composite material.
[0025] In the process of preparing the modified starch-epoxy vegetable oil composite system, triphenylphosphine and hydroquinone are used as polymerization inhibitors to prevent the hydroxyl groups generated after the chain reaction of the vegetable oil molecules from continuing to react with the system, generating a three-dimensional network structure, inhibiting the ring-opening reaction of the epoxy group, and capturing the free radicals or stable ion intermediates generated in the reaction to prevent the chain reaction from proceeding. In the subsequent mixing process with the polyhydroxyalkanoate base, microcrystalline wax, and hydrophobic plasticizer components, the vegetable oil component in the system can make the composite have better processing properties, and the vegetable oil component can also react with the microcrystalline wax during the mixing process to gel during the melting process, preventing the oil-based component from being seriously precipitated during the extrusion process, and reducing the degradation of the polyhydroxyalkanoate during the melting process, resulting in the problem of material quality degradation, and no difficult-to-degrade components are introduced in the process, while retaining the biocompatibility and degradable characteristics of the polyhydroxyalkanoate, and making the material have better mechanical properties such as toughness and strength, so that it can adapt to a wider range of processing methods. DETAILED DESCRIPTION
[0026] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] The soybean oil and castor oil used in the following examples and comparative examples were provided by Shandong Lingchuang Biotechnology Co., Ltd., and the microcrystalline wax was provided by Jiangsu Runfeng Synthetic Technology Co., Ltd.; the sulfuric acid used was pure sulfuric acid with a purity of 98%;
[0028] The debranched starch used is prepared by the following steps:
[0029] Ordinary corn starch (provided by Shanghai Jizhi Biochemical Technology Co., Ltd., CAS No.: 9005-25-8) was dissolved in 0.01 mol / L acetic acid solution at a mass volume ratio of 1g:10mL. After stirring evenly, the system temperature was raised to 80℃ and treated for 30 minutes. Then, it was incubated at 130℃ for 1 hour and then cooled to 55℃. 12U / g of pullulanase (Xiasheng Beijing Biotechnology Development Co., Ltd.) was added to the system at a volume mass ratio of 20mL:1g. After hydrolysis for 3 hours, it was heat treated at 100℃ for 30 minutes and spray dried with a flow rate of 20mL / min, an inlet temperature of 80℃, and an outlet temperature of 40℃.
[0030] The poly 3-hydroxybutyrate used was provided by Shanghai Jizhi Biochemical Technology Co., Ltd. with CAS number 26744-04-7 and product number P13980.
[0031] Example 1
[0032] A method for preparing a starch-polyhydroxyalkanoate-based degradable composite material comprises the following steps:
[0033] S1. epoxidizing the vegetable oil to obtain epoxidized vegetable oil, the specific operation is as follows:
[0034] 1 mL of sulfuric acid was added to 50 g of soybean oil and stirred evenly. Then, 5 mL of formic acid was added to the system. The system temperature was raised to 40°C and stirred at 300 rpm for 10 minutes. Then, the system temperature was raised to 55°C. 30 mL of 30 wt% hydrogen peroxide solution was added dropwise at a rate of 0.1 mL / sec. After the addition was completed, the reaction was continued for 3 hours and then allowed to stand for stratification, and the oil phase was collected. After the oil phase was washed three times with 0.1 mol / L sodium hydroxide solution, the oil phase was continued to be washed with saturated salt water until the pH value of the washing solution was 7, thereby obtaining epoxidized vegetable oil.
[0035] S2. Using the epoxidized vegetable oil in step S1 to hydrophobically modify starch to obtain a modified starch-epoxidized vegetable oil composite system, the specific operation is as follows:
[0036] The polymerization inhibitor is obtained by mixing triphenylphosphine and hydroquinone in a mass ratio of 10:0.5, and then 0.5 g of debranched starch is added to 10 mL of tetrahydrofuran, and stirred at room temperature until uniform to obtain a starch suspension; then 0.0105 g of the polymerization inhibitor is added to the system, and after the system temperature is increased to 80°C, 1 g of epoxidized vegetable oil is added, and the reaction is stirred at a rate of 30 rpm for 5 hours, and the filtrate and the filtrate are collected respectively, and the filtrate and the filtrate are washed with tetrahydrofuran respectively, and the washed filtrate is dried at 90°C, and the organic phase is removed from the washed filtrate, and the filtrate is remixed with the filtrate to obtain a modified starch-epoxidized vegetable oil composite system;
[0037] S3, 50g modified starch-epoxy vegetable oil composite system, 10g polyhydroxyalkanoate and 5g hydrophobic plasticizer are mixed in a blender at a rate of 100rpm for 5 minutes, 0.65g microcrystalline wax is added, the stirring rate is then increased to 500rpm, and stirring is continued for 10 minutes to obtain a mixture; wherein, polyhydroxyalkanoate is poly 3-hydroxybutyrate (PHB), and hydrophobic plasticizer is triethyl citrate. The mixture is sealed and placed at room temperature for 24 hours, and then extruded and granulated by a twin-screw granulator, and the temperature and head temperature of the granulator from zone 1 to zone 5 are respectively set to 120°C, 150°C, 160°C, 165°C, 160°C and 130°C, and the screw speed is 45rpm, to obtain a starch-polyhydroxyalkanoate-based degradable composite material.
[0038] Example 2
[0039] A method for preparing a starch-polyhydroxyalkanoate-based degradable composite material comprises the following steps:
[0040] S1. epoxidizing the vegetable oil to obtain epoxidized vegetable oil, the specific operation is as follows:
[0041] Add 2 mL of sulfuric acid to 50 g of soybean oil and stir evenly. Then add 6.2 mL of formic acid to the system, raise the system temperature to 45 ° C and stir at 400 rpm for 10 minutes, then raise the system temperature to 60 ° C, add 35 mL of 30 wt% hydrogen peroxide solution at a rate of 2 drops / second, continue to react for 3 hours after the addition is complete, let stand and separate, and collect the oil phase; wash the oil phase three times with 0.1 mol / L sodium hydroxide solution, and then continue to wash the oil phase with saturated brine until the pH value of the washing solution is 7, so as to obtain epoxidized vegetable oil.
[0042] S2. Using epoxidized vegetable oil to hydrophobically modify starch to obtain a modified starch-epoxidized vegetable oil composite system, the specific operation is as follows:
[0043] The polymerization inhibitor is obtained by mixing triphenylphosphine and hydroquinone in a mass ratio of 15:2, and then 0.75g of debranched starch is added to 10mL of tetrahydrofuran, and stirred at room temperature until uniform to obtain a starch suspension; then 0.017g of the polymerization inhibitor is added to the system, and after the system temperature is increased to 90°C, 5g of epoxidized vegetable oil is added, and the reaction is stirred at a rate of 45rpm for 12 hours, and the filtrate and the filtrate are collected respectively, and the filtrate and the filtrate are washed with tetrahydrofuran respectively, and the washed filtrate is dried at 90°C, and the organic phase is removed from the washed filtrate, and the filtrate is remixed with the filtrate to obtain a modified starch-epoxidized vegetable oil composite system;
[0044] S3, 55g modified starch-epoxy vegetable oil composite system, 15g polyhydroxyalkanoate and 7g hydrophobic plasticizer were mixed in a blender at a rate of 120rpm for 10 minutes, 2.31g microcrystalline wax was added, and the stirring rate was subsequently increased to 600rpm, and stirring was continued for 15 minutes to obtain a mixture; wherein, polyhydroxyalkanoate is poly 3-hydroxybutyrate (PHB), and hydrophobic plasticizer is ethyl lactate. The mixture was sealed and placed at room temperature for 24 hours, and then extruded and granulated by a twin-screw granulator, and the temperature of the granulator from zone 1 to zone 5 and the head temperature were set to 120℃, 150℃, 160℃, 165℃, 160℃ and 130℃, respectively, and the screw speed was 45rpm, to obtain a starch-polyhydroxyalkanoate-based degradable composite material.
[0045] Example 3
[0046] A method for preparing a starch-polyhydroxyalkanoate-based degradable composite material comprises the following steps:
[0047] S1. epoxidizing the vegetable oil to obtain epoxidized vegetable oil, the specific operation is as follows:
[0048] 3 mL of sulfuric acid was added to 50 g of castor oil and stirred evenly, and then 7 mL of formic acid was added to the system, the system temperature was raised to 50° C. and stirred at 500 rpm for 10 minutes, and then the system temperature was raised to 65° C., and 40 mL of 30 wt% hydrogen peroxide solution was added dropwise at a rate of 0.1 mL / s. After the addition was completed, the reaction was continued for 3 hours, and then the mixture was allowed to stand and decomposed, and the oil phase was collected; the oil phase was washed three times with 0.1 mol / L sodium hydroxide solution, and then the oil phase was continued to be washed with saturated salt water until the pH value of the washing solution was 7, thereby obtaining epoxidized vegetable oil;
[0049] S2. Using the epoxidized vegetable oil in step S1 to hydrophobically modify starch to obtain a modified starch-epoxidized vegetable oil composite system, the specific operation is as follows:
[0050] The polymerization inhibitor was obtained by mixing triphenylphosphine and hydroquinone in a mass ratio of 20:5.
[0051] 1 g of debranched starch was added to 10 mL of tetrahydrofuran, and stirred at room temperature until uniform to obtain a starch suspension; then 0.025 g of an inhibitor was added to the system, and the system temperature was increased to 100° C., and then 10 g of epoxidized vegetable oil was added, and the reaction was stirred at a rate of 60 rpm for 20 hours, and the filtrate and the filtrate were collected respectively to be cooled to room temperature, and the filtrate and the filtrate were washed with tetrahydrofuran respectively, and the washed filtrate was dried at 90° C., and the organic phase was removed from the washed filtrate, and the filtrate was remixed with the filtrate to obtain a modified starch-epoxidized vegetable oil composite system;
[0052] S3. Mix 60g of modified starch-epoxy vegetable oil composite system, 20g of polyhydroxyalkanoate and 10g of hydrophobic plasticizer in a blender at 150rpm for 10 minutes, add 4.5g of microcrystalline wax, then increase the stirring speed to 700rpm, and continue mixing for 20 minutes to obtain a mixture; wherein the polyhydroxyalkanoate is poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (P(3HB-co-3mol%3HV)), and the hydrophobic plasticizer is triethyl citrate. The mixture is sealed and placed at room temperature for 24 hours, and then extruded and granulated by a twin-screw granulator. The temperatures of zones 1 to 5 and the head temperature of the granulator are set to 120℃, 150℃, 160℃, 165℃, 160℃ and 130℃, respectively, and the screw speed is 45rpm, to obtain a starch-polyhydroxyalkanoate-based degradable composite material.
[0053] Comparative Example 1
[0054] A method for preparing a starch-polyhydroxyalkanoate-based degradable composite material comprises the following steps:
[0055] S1. epoxidizing the vegetable oil to obtain epoxidized vegetable oil, the specific operation is as follows:
[0056] 1 mL of sulfuric acid was added to 50 g of soybean oil and stirred evenly. Then, 5 mL of formic acid was added to the system. The system temperature was raised to 40°C and stirred at 300 rpm for 10 minutes. Then, the system temperature was raised to 55°C. 30 mL of 30 wt% hydrogen peroxide solution was added dropwise at a rate of 0.1 mL / s. After the addition was completed, the reaction was continued for 3 hours and then allowed to stand for stratification, and the oil phase was collected. After the oil phase was washed three times with 0.1 mol / L sodium hydroxide solution, the oil phase was continued to be washed with saturated brine until the pH value of the washing solution was 7, thereby obtaining epoxidized vegetable oil.
[0057] S2, 16.67g starch and 33.33g epoxidized vegetable oil, 10g polyhydroxyalkanoate and 5g hydrophobic plasticizer are mixed in a stirrer at a rate of 100rpm for 5 minutes, 0.65g microcrystalline wax is added and the stirring rate is subsequently increased to 500rpm to obtain a mixture; wherein, polyhydroxyalkanoate is poly-3-hydroxybutyrate (PHB), and hydrophobic plasticizer is triethyl citrate. The mixture is sealed and placed for 24 hours at room temperature, and then extruded and granulated by a twin-screw granulator, and the temperature and head temperature of the granulator from zone 1 to zone 5 are respectively set to 120°C, 150°C, 160°C, 165°C, 160°C and 130°C, and the screw speed is 45rpm, to obtain a starch-polyhydroxyalkanoate-based degradable composite material.
[0058] Comparative Example 2
[0059] A method for preparing a starch-polyhydroxyalkanoate-based degradable composite material comprises the following steps:
[0060] S1, 16.67g starch and 33.33g soybean oil, 10g polyhydroxyalkanoate and 5g hydrophobic plasticizer were mixed in a blender at a rate of 100rpm for 5 minutes, 0.65g microcrystalline wax was added and the stirring rate was subsequently increased to 500rpm to obtain a mixture; wherein, polyhydroxyalkanoate is poly 3-hydroxybutyrate (PHB), and hydrophobic plasticizer is triethyl citrate. The mixture was sealed and placed at room temperature for 24 hours, and then extruded and granulated by a twin-screw granulator, and the temperature and head temperature of the granulator from zone 1 to zone 5 were set to 120°C, 150°C, 160°C, 165°C, 160°C and 130°C, respectively, and the screw speed was 45rpm, to obtain a starch-polyhydroxyalkanoate-based degradable composite material.
[0061] Comparative Example 3
[0062] A method for preparing a starch-polyhydroxyalkanoate-based degradable composite material comprises the following steps:
[0063] S1. epoxidizing the vegetable oil to obtain epoxidized vegetable oil, the specific operation is as follows:
[0064] 1 mL of sulfuric acid was added to 50 g of soybean oil and stirred evenly. Then, 5 mL of formic acid was added to the system. The system temperature was raised to 40°C and stirred at 300 rpm for 10 minutes. Then, the system temperature was raised to 55°C. 30 mL of 30 wt% hydrogen peroxide solution was added dropwise at a rate of 0.1 mL / s. After the addition was completed, the reaction was continued for 3 hours and then allowed to stand for stratification, and the oil phase was collected. After the oil phase was washed three times with 0.1 mol / L sodium hydroxide solution, the oil phase was continued to be washed with saturated brine until the pH value of the washing solution was 7, thereby obtaining epoxidized vegetable oil.
[0065] S2. Using the epoxidized vegetable oil in step S1 to hydrophobically modify starch to obtain a modified starch-epoxidized vegetable oil composite system, the specific operation is as follows:
[0066] The polymerization inhibitor is obtained by mixing triphenylphosphine and hydroquinone in a mass ratio of 10:0.5, and then 0.5 g of debranched starch is added to 10 mL of tetrahydrofuran, and stirred at room temperature until uniform to obtain a starch suspension; then 0.0105 g of the polymerization inhibitor is added to the system, and after the system temperature is increased to 80°C, 1 g of epoxidized vegetable oil is added, and the reaction is stirred at a rate of 30 rpm for 5 hours, and the filtrate and the filtrate are collected respectively, and the filtrate and the filtrate are washed with tetrahydrofuran respectively, and the washed filtrate is dried at 90°C, and the organic phase is removed from the washed filtrate, and the filtrate is remixed with the filtrate to obtain a modified starch-epoxidized vegetable oil composite system;
[0067] S3, 50g modified starch-epoxy vegetable oil composite system, 10g polyhydroxyalkanoate and 5.65g hydrophobic plasticizer were mixed in a stirrer at a rate of 100rpm for 5 minutes, and then the stirring rate was increased to 500rpm to obtain a mixture; wherein the polyhydroxyalkanoate was poly-3-hydroxybutyrate (PHB) and the hydrophobic plasticizer was triethyl citrate. The mixture was sealed and placed at room temperature for 24 hours, and then extruded and granulated by a twin-screw granulator, and the temperature of the granulator zone 1 to zone 5 and the head temperature were set to 120°C, 150°C, 160°C, 165°C, 160°C and 130°C, respectively, and the screw speed was 45rpm, to obtain a starch-polyhydroxyalkanoate-based degradable composite material.
[0068] Comparative Example 4
[0069] A method for preparing a starch-polyhydroxyalkanoate-based degradable composite material comprises the following steps:
[0070] S1. epoxidizing the vegetable oil to obtain epoxidized vegetable oil, the specific operation is as follows:
[0071] 1 mL of sulfuric acid was added to 50 g of soybean oil and stirred evenly. Then, 5 mL of formic acid was added to the system. The system temperature was raised to 40°C and stirred at 300 rpm for 10 minutes. Then, the system temperature was raised to 55°C. 30 mL of 30 wt% hydrogen peroxide solution was added dropwise at a rate of 0.1 mL / s. After the addition was completed, the reaction was continued for 3 hours and then allowed to stand for stratification, and the oil phase was collected. After the oil phase was washed three times with 0.1 mol / L sodium hydroxide solution, the oil phase was continued to be washed with saturated brine until the pH value of the washing solution was 7, thereby obtaining epoxidized vegetable oil.
[0072] S2. Using the epoxidized vegetable oil in step S1 to hydrophobically modify starch to obtain a modified starch-epoxidized vegetable oil composite system, the specific operation is as follows:
[0073] The polymerization inhibitor is obtained by mixing triphenylphosphine and hydroquinone in a mass ratio of 10:0.5, and then 0.5 g of debranched starch is added to 10 mL of tetrahydrofuran, and stirred at room temperature until uniform to obtain a starch suspension; then 0.0105 g of the polymerization inhibitor is added to the system, and after the system temperature is increased to 80°C, 1 g of epoxidized vegetable oil is added, and the reaction is stirred at a rate of 30 rpm for 5 hours, and the filtrate and the filtrate are collected respectively, and the filtrate and the filtrate are washed with tetrahydrofuran respectively, and the washed filtrate is dried at 90°C, and the organic phase is removed from the washed filtrate, and the filtrate is remixed with the filtrate to obtain a modified starch-epoxidized vegetable oil composite system;
[0074] S3, 50g of modified starch-epoxy vegetable oil composite system, 10g of polyhydroxyalkanoate and 5.65g of plasticizer were mixed in a mixer at a speed of 100rpm for 5 minutes, and then the stirring speed was increased to 500rpm to obtain a mixture; wherein the polyhydroxyalkanoate is poly 3-hydroxybutyrate (PHB) and the plasticizer is glycerol. The mixture was sealed and placed at room temperature for 24 hours, and then extruded and granulated by a twin-screw granulator. The temperature of the first to fifth zones of the granulator and the head temperature were set to 120℃, 150℃, 160℃, 165℃, 160℃ and 130℃ respectively, and the screw speed was 45rpm, thus obtaining a starch-polyhydroxyalkanoate-based degradable composite material.
[0075] The mechanical properties of the composite materials prepared in Examples 1-3 and Comparative Examples 1-4 were tested. The composite materials prepared in different groups were injected into a hot press machine to prepare a film sample with a thickness of 0.8 mm, and then placed at 23°C and 53% relative humidity for one week, and then cut to obtain a sample of 1.5 cm*10 cm in size. The tensile strength and elongation at break of the sample were then tested using a physical property tester to determine the mechanical properties of the material. The initial clamping distance of the probe was 100 mm, and the probe moving rate was 100 mm / min. Five readings were obtained for each sample and the average value was taken. The test results are shown in Table 1 below.
[0076] Table 1 Mechanical properties test of composite materials prepared in Examples 1-3 and Comparative Examples 1-4
[0077]
[0078] From the results in Table 1, it can be seen that the composite material prepared in Example 2 has the best tensile strength and elongation at break. From the results in Comparative Examples 1 and 2, it can be seen that epoxidizing vegetable oil and then reacting it with starch can increase the compatibility of starch and PHA materials and improve its mechanical properties such as tensile strength and elongation at break. From the results in Comparative Examples 3 and 4, it can be seen that the system formed by wax and vegetable oil during the preparation process can reduce the precipitation of vegetable oil and improve the plasticizing effect of vegetable oil on the PHA-starch body. Other commonly used plasticizers for PHA, represented by glycerol, have poor compatibility in the system and cannot exert a good plasticizing effect.
[0079] Now the thermal stability test is carried out on the composite materials prepared in Examples 1-3 and Comparative Examples 1-4. The composite materials prepared in different groups are injected into a hot press machine to prepare a film sample with a thickness of 0.8 mm, and then placed at 23°C and 53% relative humidity for one week, and then cut to obtain a sample with a mass of 10±0.2 mg. Then, a thermogravimetric analyzer is used to increase the temperature from 25°C to 600°C in a nitrogen atmosphere at a heating rate of 10°C / min, and the thermal weight loss of the composite film is measured, and the temperature at which the sample mass loses 20% is recorded. The film sample is placed in a differential calorimeter scanner, and the temperature is increased from -50°C to 250°C in a nitrogen atmosphere at a heating rate of 10°C / min in a nitrogen atmosphere. The melting start temperature and melting peak temperature of the composite material are measured to determine the thermal stability of the material. Five readings are obtained for each sample and the average value is taken. The test results are shown in Table 2 below.
[0080] Table 2 Thermal stability test of the composite materials prepared in Examples 1-3 and Comparative Examples 1-4
[0081]
[0082] As can be seen from the results in Table 2, the composite material prepared in Example 2 has the highest thermal weight loss temperature, and at the same time has the highest melting onset temperature and melting peak temperature difference, and is least likely to lose structure during the melting process. As can be seen from the data in Comparative Examples 1-2, the epoxidized vegetable oil and starch are reacted and then blended, which can improve the stability of the components in the blending system, and the direct use of epoxidized vegetable oil can also react with the PHA matrix containing hydroxyl groups and debranched starch to improve the binding effect of the system and make it have higher thermal stability. As can be seen from the results in Comparative Example 3, the system formed by vegetable oil and microcrystalline wax during the melting process can improve the thermal stability of the composite material as a whole and reduce its thermal decomposition temperature. As can be seen from the results in Comparative Example 4, the use of hydrophobic plasticizers such as citrate has an enhancing effect on the system.
[0083] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0084] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A method for preparing a starch-polyhydroxyalkanoate-based biodegradable composite material, characterized in that: The following steps are involved: S1. epoxidizing the vegetable oil to obtain epoxidized vegetable oil, the specific operation is as follows: Add sulfuric acid to the vegetable oil and stir evenly, then add formic acid to the system, raise the system temperature to 40-50°C and stir at a rate of 300-500rpm for 5-20 minutes, then raise the system temperature to 55-65°C, dropwise add hydrogen peroxide solution at a rate of 1-2 drops / second, continue to react for 2-4 hours after the dropwise addition is completed, stand and separate, and collect the oil phase; wash the oil phase with sodium hydroxide solution and saturated salt water in turn to obtain epoxidized vegetable oil; S2. Using epoxidized vegetable oil to hydrophobically modify starch to obtain a modified starch-epoxidized vegetable oil composite system, the specific operation is as follows: Add debranched starch to tetrahydrofuran, and stir at room temperature until uniform to obtain a starch suspension; then add an inhibitor to the system, raise the system temperature to 80-100° C., add the epoxidized vegetable oil prepared in step S1, and stir to react for 5-20 hours, then cool the system to room temperature and collect the filtrate and the filtrate, respectively, wash the filtrate and the filtrate with tetrahydrofuran, dry the washed filtrate, remove the organic phase from the washed filtrate, and remix with the filtrate to obtain a modified starch-epoxidized vegetable oil composite system; The polymerization inhibitor is prepared by mixing triphenylphosphine and hydroquinone in a mass ratio of (10-20): (0.5-5); S3. Mix the modified starch-epoxidized vegetable oil composite system, polyhydroxyalkanoate and hydrophobic plasticizer in a blender at a mass ratio of (50-60):(10-20):(5-10) at a speed of 100-150 rpm for 5-10 minutes, add microcrystalline wax and then increase the stirring speed to 500-700 rpm, and continue mixing for 10-20 minutes to obtain a mixture; seal the mixture and place it at room temperature for 12-36 hours, and then extrude and granulate it through a twin-screw granulator at a screw speed of 30-60 rpm to obtain a starch-polyhydroxyalkanoate-based biodegradable composite material.
2. The method for preparing a starch-polyhydroxyalkanoate-based degradable composite material according to claim 1, characterized in that: In step S1, the volume ratio of sulfuric acid, formic acid, hydrogen peroxide solution and vegetable oil is (1-3):(5-7):(30-40):
50.
3. The method for preparing a starch-polyhydroxyalkanoate-based degradable composite material according to claim 1, characterized in that: The mass ratio of debranched starch, epoxidized vegetable oil and inhibitor is (0.5-1):(1-5):(0.0105-0.025).
4. The method for preparing a starch-polyhydroxyalkanoate-based degradable composite material according to claim 1, characterized in that: In step S3, the hydrophobic plasticizer is at least one of a citrate plasticizer and a lactate plasticizer.
5. The method for preparing a starch-polyhydroxyalkanoate-based degradable composite material according to claim 1, characterized in that: In step S3, the amount of microcrystalline wax used is 1-5wt% of the total mass of the modified starch-epoxidized vegetable oil composite system, polyhydroxyalkanoate and hydrophobic plasticizer.
6. A material obtained by the method for preparing a starch-polyhydroxyalkanoate-based degradable composite material as claimed in any one of claims 1 to 5.
Citation Information
Patent Citations
Starch-based alloy environment-friendly material and preparation method thereof
CN112391043A
Waterproof starch-based straw and preparation method thereof
CN116574313A
Biodegradable polymeric material, biodegradable product and manufacturing method and application thereof
CN117480215A